2016
DOI: 10.1177/0271678x16667953
|View full text |Cite
|
Sign up to set email alerts
|

Application of optical methods in the monitoring of traumatic brain injury: A review

Abstract: We present an overview of the wide range of potential applications of optical methods for monitoring traumatic brain injury. The MEDLINE database was electronically searched with the following search terms: “traumatic brain injury,” “head injury,” or “head trauma,” and “optical methods,” “NIRS,” “near-infrared spectroscopy,” “cerebral oxygenation,” or “cerebral oximetry.” Original reports concerning human subjects published from January 1980 to June 2015 in English were analyzed. Fifty-four studies met our inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 118 publications
(164 reference statements)
0
53
0
Order By: Relevance
“…25e28 To solve this contradiction, some authors argued that, during brain death, oxygenated blood may be somehow compartmentalised in the brain, so that the NIRS assessment of normal oxygenation in a nonperfused brain could be correct. 2,3,29 This hypothesis, however, conflicts with several lines of evidence in animals and in a limited number of human reports. Brain death is the result of progressive global cerebral ischaemia, in which raised intracranial pressure reduces cerebral perfusion pressure (CPP) and consequently CBF.…”
Section: Discussionmentioning
confidence: 64%
“…25e28 To solve this contradiction, some authors argued that, during brain death, oxygenated blood may be somehow compartmentalised in the brain, so that the NIRS assessment of normal oxygenation in a nonperfused brain could be correct. 2,3,29 This hypothesis, however, conflicts with several lines of evidence in animals and in a limited number of human reports. Brain death is the result of progressive global cerebral ischaemia, in which raised intracranial pressure reduces cerebral perfusion pressure (CPP) and consequently CBF.…”
Section: Discussionmentioning
confidence: 64%
“…The superscript indicates that absorption values obtained at iteration k were used. The reconstructed absorption will be the result of adding all δµ a to the initial absorption estimation, that is, µ a = δµ (1) a + δµ (2) a + . .…”
Section: Time-and Datatypes-based Reconstructionmentioning
confidence: 99%
“…Time-resolved diffuse optical technology is an emerging photonic technique to continuously quantify the concentrations of several physiological chromophores such as hemoglobin, lipid or collagen. Successful measurements have been done at different human body locations such as brain [1,2], breast [3] or thyroid [4]. An interesting extension of this technology is to perform diffuse optical tomography [5,6] by computing three-dimensional maps of oxy-and deoxy-hemoglobin; in this approach, photon propagation is modeled in a computer and results are compared with experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In this same patient population, Ono [21] et al later found that not only was autoregulation was impaired, but a significant correlation between cerebral autoregulatory values in NIRS and mean velocity indices of TCDs. In fact, Weigl's [22] 2016 meta-analysis on the application of optical methods in the monitoring of TBI supports the use of NIRS for the assessment of cerebral autoregulation and described the use of targeted individual autoregulation guided treatment of patients with TBI at the bedside. …”
Section: Berry Et Al Journal Of Behavioral and Brain Sciencementioning
confidence: 99%